For converting Slope intercept to standard form, we use following steps -
Step 1: As we all know that, slope intercept form equation in mathematics is y = mx + K, where ‘m’ is a Slope of given line and ‘K’ is a constant. So, first of all we calculate slope ‘m’ and constant ‘K’ form slope intercepts form.
Step 2 : After evaluation of slope intercepts form, now we shift all variables to one side and constants to other side, like we have a slope intercepts form y = 7x + 11, then
y = 7x + 11,
=> y – 7x = 11 or 7x – y = -11,
These are two possible standard forms of a given line equation.
Now we take an example to understand the process of converting slope intercept to standard form -
Example: Convert the given slope intercepts form into standard form -
y = (4 / 3) x + 12?
Solution: We use following steps to evaluate standard form from Slope Intercept Form-
Step 1: First of all, we analyze given slope intercept form-
y = (4 / 3)x + 12,
Here slope = m = (4 / 3) and constant K = 12,
Step 2: Now we shift variables on one side and constants on other side -
y = (4 / 3) x + 12,
=> y – (4 / 3) x = 12 or (4 / 3) x – y = -12,
=> 3y – 4x = 36 or 4x – 3y = -36
So, these are two possible standard forms are generated from slope intercept form.
Therefore these two steps are useful for converting slope intercepts form to standard form.